Assessing Food Safety Challenges in Indonesia’s Free Nutrition Meal Program: Causes and Solutions to Foodborne Illnesses - Rajagopal, Ranjini; Rajesh, Kokila (Takaza Innovatix Labs Ltd., 2025)
This study investigates the food safety issues within Indonesia's Free Nutrition Meal (MBG) program, which provides meals to children in schools, and analyzes the causes of foodborne illness outbreaks. A quantitative research methodology was employed, utilizing a cross-sectional survey of schools participating in the MBG program to assess food safety practices, frequency of foodborne illness cases, and other relevant factors. The findings indicate that foodborne illnesses were prevalent, driven by inadequate food safety practices, improper food handling, insufficient training for food handlers, and insufficient food storage and transportation infrastructure. Additionally, the study highlights the role of regulatory oversight by the Indonesian National Food and Drug Agency (BPOM), which faces challenges in enforcing food safety standards at the local level. The study concludes by recommending improvements in food safety training, infrastructure, and regulatory enforcement to ensure the health and safety of children benefiting from the program.